2011
DOI: 10.1038/bjc.2011.86
|View full text |Cite
|
Sign up to set email alerts
|

Randomised phase II trial of gemcitabine plus vinorelbine vs gemcitabine plus cisplatin vs gemcitabine plus capecitabine in patients with pretreated metastatic breast cancer

Abstract: Background:An increasing proportion of patients are exposed to anthracyclines and/or taxanes in the adjuvant or neoadjuvant setting. Re-exposure in the metastatic stage is limited by drug resistance, thus evaluation of non-cross-resistant regimens is mandatory.Methods:Anthracycline-pretreated patients were randomly assigned to three gemcitabine-based regimens. Chemotherapy consisted of gemcitabine 1.000 mg m−2 plus vinorelbin 25 mg m−2 on days 1+8 (GemVin), or plus cisplatin 30 mg m−2 on days 1+8 (GemCis), or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 53 publications
4
26
1
2
Order By: Relevance
“…Several randomized phase II and III studies have been conducted for MBC patients evaluating the combination therapy versus monotherapy or sequential therapy, and they reported conflicting results [34,35,36,37]. In a phase III trial, the combination therapy was superior to the single agent vinorelbine in both PFS and ORR, with manageable toxicities; however, there was no difference in OS, and the regimen led to more hematologic toxicities [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several randomized phase II and III studies have been conducted for MBC patients evaluating the combination therapy versus monotherapy or sequential therapy, and they reported conflicting results [34,35,36,37]. In a phase III trial, the combination therapy was superior to the single agent vinorelbine in both PFS and ORR, with manageable toxicities; however, there was no difference in OS, and the regimen led to more hematologic toxicities [37].…”
Section: Discussionmentioning
confidence: 99%
“…In a phase II study comparing gemcitabine and vinorelbine combination therapy with sequential monotherapy (gemcitabine followed by vinorelbine), there was no difference in efficacy between the two arms, but patients in the combination arm experienced an improved quality of life with similar adverse events [36]. In a randomized phase II trial comparing gemcitabine plus vinorelbine, gemcitabine plus cisplatin, and gemcitabine plus carboplatin in pretreated MBC patients, no significant differences were found between these arms regarding treatment efficacy [35]. Another phase III study of combined vinorelbine and gemcitabine versus single-agent capecitabine demonstrated no superiority of the combined therapy over the single agent regarding ORR, PFS, and OS [34].…”
Section: Discussionmentioning
confidence: 99%
“…A polychemotherapy regimen found active both in pancreatic cancer [12] and breast cancer [13,14] was selected as neoadjuvant chemotherapy for the pancreatic cancer and as adjuvant chemotherapy for the breast tumor. We speculate that the role of the inherited gene mutation can not be excluded in the unexpectedly good response of the advanced pancreatic and breast cancers to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Other non-cross-resistant agents such as gemcitabine and vinorelbine are used as single agents after failure of anthracycline/taxane in TNBC, with pCR rates ranging from 28 to 40% compared to 3-14% without gemcitabine or vinorelbine [55][56][57]. Epothilone B ixabepilone and Eribulin recently gained FDA approval for the treatment of advanced disease and have been shown to be efficacious in TNBC patients [58,59].…”
Section: Metastatic Diseasementioning
confidence: 99%